Asuhan Keperawatan Pada Ibu Post Partum Sectio Caesarea Dengan Penyulit Malpresentasi Janin di Rumah Sakit Wilayah Kerja Depok - Ayu Zaharany, Tsania (Indonesian Journal of Nursing Scientific, 2022)
ABSTRACT Background: Fetal malpresentation is the most common indication for cesarean section with an incidence rate of 52.3%. The risk of fetal malpresentation in multiparous mothers is five times greater than in primiparous mothers. There is an impact after post op sectio caesarea which includes the emergence of pain, reduced mobility of the mother due to incisional wounds, so the role of nurses is needed in the nursing care process so that the various impacts of these conditions can be overcome. Objective: To describe and apply nursing care to post partum sectio caesarea mothers with complications of fetal malpresentation. Methods: This case study uses an analytical descriptive method, with 2 subjects conducted based on a comprehensive nursing care approach from assessment to evaluation. Results: After nursing care for 3x24 hours, from the results of the assessment, it was found that both patients experienced pain. In both patients, there were also 3 same diagnoses and 1 different diagnosis with priority diagnosis in both patients, namely acute pain. The acute pain nursing problem in both patients could be resolved on the third day of treatment so that the intervention could be discontinued. Conclusion: In both postoperative sectio caesarea patients with priority acute pain nursing problems, there is the ability to carry out pain management in the process of implementing nursing care. Keywords: Nursing Care, Sectio Caesarea, Fetal Malpresentation